Current innovative approaches in reducing polycyclic aromatic hydrocarbons (PAHs) in processed meat and meat products - Arun K. Das; Dipanwita Bhattacharya; Annada Das; Santanu Nath; Samiran Bandyopadhyay; Pramod Kumar Nanda; Mohammed Gagaoua (Chemical and Biological Technologies in Agriculture, 2023)
Abstract The presence of polycyclic aromatic hydrocarbons (PAHs) in processed meat and meat products is a global concern as they are known to be carcinogenic, mutagenic, teratogenic, and genotoxic to living beings. PAHs are generated in processed meat through different thermo-processing techniques, such as smoking, grilling, barbecuing, roasting, and frying, which involve abnormal high-temperature treatments and extruded fuels. These carbonaceous compounds with two or more cyclic benzene rings are highly stable and toxic, and their generation is enhanced by faulty thermal processing techniques, contaminated raw materials, and environmental pollution. Based on their degree of toxicity, Benzo[a]pyrene (B[a]P) is recognized as the most probable human carcinogen among different fractions of PAHs by the European Commission Regulation (EC-No.1881/2006). Furthermore, the association between dietary PAHs exposures and their role as carcinogen in human beings has been reported clinically. Therefore, it is necessary to focus on prevention and control of PAHs formation in processed meat products through various strategies to avert public health concerns and safety issues. Accordingly, several approaches have been used to reduce the risk of PAHs formation by employing safe processing systems, harmless cooking methods, marination by natural plant components, use of biological methods etc. to eliminate or reduce the harmful effects of PAHs in the food system. This review provides a comprehensive insight into the occurrence and formation of PAHs in meat and meat products and their toxicological effects on human beings. Furthermore, the different cost-effective and environment friendly methods that have been employed as “green strategies” to mitigate PAHs in meat and meat products at both household and commercial levels are discussed. Graphical Abstract